Homophone and Homograph of The Lexical Ambiguity in Dune Movie - Tasha Amelyana; Winda Lutfiyanti; Esterria Romauli (Sekolah Tinggi Bahasa Asing JIA, 2022)
The purpose of this research is to find words that are included into Homophone and Homograph in Dune movie subtitles. A qualitative method was applied to this research, by obtaining data from watching movies and observing subtitles, then taking screenshots with subtitles that have Homophone or Homograph in them, along with analyzing the words with Cambridge and Oxford dictionaries as references. The information from these dictionaries is used to verify meaning, pronunciation and spelling of the data found. This research applied the theory of Hobbs (2006) and Fox (1995). Based on the result of data analysis, some homophone words found in this movie are air – heir, been – bean, weather – whether, by – buy – bye, and many more. Meanwhile, some homograph words found in this movie are use, desert, lead, and live. Thus, there are 33 data found with a higher number of Homophone words (29 words) and Homograph (4 words).